Environmental and toxicology variables of pesticides used in Integrated Apple Production (IAP) focusing matematical modeling - Gebler, Luciano; Pelizza, Tânia Regina; Almeida, Daniele Lisboa de (Revista de Ciências Agroveterinárias, 2006)
Some reasons for the low use of mathematical modeling to control the agricultural environment in Integrated Apple Production (IAP) are the lack of software fitted to Brazilian conditions, the absence of Portuguese language software and the difficulty to obtain data used in such models. The objective of this review is to provide physical-chemical and toxicological data of pesticides used in IAP until 2005/2006 harvest in a single document, easing the access to these data.